Rapidly Growing Bilateral Pseudoangiomatous Stromal Hyperplasia of the Breast - Ryu, Eun Mi (The Korean Society of Radiology, 2010)
A tumoral pseudoangiomatous stromal hyperplasia (PASH) that causes huge breast enlargement is very rare. Only two cases of huge tumoral PASHs have been reported in the English medical literature. We report here on a surgically confirmed case of bilateral huge tumoral PASH in a 47-year-old woman, and we present the imaging and histopathology findings. We also review the relevant medical literature.